1994
DOI: 10.1101/gad.8.23.2891
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for the 60-kD Ro autoantigen in a discard pathway for defective 5S rRNA precursors.

Abstract: The Ro autoantigen is a 60-kD protein that is usually found in small cytoplasmic RNA-protein complexes known as Ro RNPs. Although the Ro RNPs are abundant and conserved components of a variety of vertebrate and invertebrate cells, their function is unknown. We have discovered that the Ro protein is also found complexed with certain variant 5S rRNAs in Xenopus oocytes. These RNAs contain one or more point mutations compared with the major oocyte 5S rRNA sequence as well as additional nucleotides at the 3' end. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 63 publications
5
157
0
2
Order By: Relevance
“…Like La, the human autoantigen Ro binds to pol III transcripts to form ribonucleoprotein particles. In the case of Ro, however, binding is specific for the pol III-transcribed Y RNAs and defective 5S rRNA molecules (39,40). The function of Ro is unclear, although the observation that it binds specifically to nonfunctional 5S transcripts suggests it may have a role in 5S rRNA quality control (40).…”
Section: The Human Autoantigen Ro Is Not Found Associated With Pol Iii-mentioning
confidence: 98%
“…Like La, the human autoantigen Ro binds to pol III transcripts to form ribonucleoprotein particles. In the case of Ro, however, binding is specific for the pol III-transcribed Y RNAs and defective 5S rRNA molecules (39,40). The function of Ro is unclear, although the observation that it binds specifically to nonfunctional 5S transcripts suggests it may have a role in 5S rRNA quality control (40).…”
Section: The Human Autoantigen Ro Is Not Found Associated With Pol Iii-mentioning
confidence: 98%
“…A molecular definition for these autoantigens has been provided by the isolation of cDNA clones (25,27). The 60-kDa SS-A/Ro protein binds to hY RNA in an in vitro reconstitution assay (25), and has been proposed to function as part of a novel quality control of discard pathway for 5S ribosomal RNA (28). Ro52, one of the components of the SS-A/Ro complex, includes two isoforms, 52-␣ and 52-␤.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant RNAs are processed inefficiently to mature 5S RNA. They are less stable than the wild-type 5S RNA precursors and eventually degrade (O'Brien and Wolin, 1994). The Ro protein binds 5S RNA precursors containing a variety of internal mutations while discriminating against the wild-type 5S RNA.…”
Section: Genome Research 139mentioning
confidence: 99%
“…In Xenopus, a well-characterized model, there is a developmental regulation of expression for the two families of 5S rRNA (Peterson et al 1980). O'Brien and Wolin (1994) have shown that the Ro protein binds specifically some mutant 5S RNA, and this protein has been proposed to function in a quality control or discard pathway for 5S rRNA synthesis in Xenopus oocytes (Shi et al 1996).…”
mentioning
confidence: 99%